Effect of graphite size on the tribological behavior of Ti (C, N)-based cermets self-mated wear pairs. (April 2017) - Liu, Junbo; Xiong, Ji; Guo, Zhixing; Yang, Tian'en; Wan, Weicai; Zhou, Liming; Ye, Junliu; Li, Tijun; Li, Shenhou
Abstract: In the present work, graphite of different particle size ranging from 2 μm to 32 μm is added into the system to lubricate the Ti (C, N) cermets, but the addition amount is fixed at 1 wt%. The sliding wear tests were carried out using block-on-ring equipment. The distribution morphology of graphite, mechanical properties and wear behavior were studied in this paper. The results indicate that when the graphite is added into the cermet, graphite particles join together and are distributed to clusters of different size which are like bird nests. The range of the "bird-nest" clusters increase with the improvement of graphite size when the graphite particle size is smaller than 12 μm but decrease when larger than 12 μm. Furthermore when the graphite grain size increase to 32 μm, most of the particles exist in the cermets individually instead of distributing like bird nest The mechanical properties decrease with the improvement of graphite size, and when the particles size of graphite increase to 32 μm the mechanical properties get worse sharply. The wear mechanism of the cermets with graphite, adhesion and plastic deformation are dominated. The extruded graphite forms a tribofilm, and protects the surface from the hard abrasive particles ploughing. When the particles size of graphite added is 22 μm, cermets which have coarser graphite particles and more but moderate-in-size graphite clusters possess the best effect of lubrication Highlights: The influence of graphite particle size on the distribution morphology of graphite particles is investigated. The influence of graphite particle size on the mechanical properties is investigated. The influence of graphite particle size on the wear behavior of cermets self-mated wear pairs is investigated.